2013
DOI: 10.1097/tgr.0b013e31828aee0d
|View full text |Cite
|
Sign up to set email alerts
|

Reliability of Ankle-Brachial Index Measurements

Abstract: An ankle-brachial index (ABI) is determined by comparing blood pressures of the extremities. No study that compared the blood pressure measurements obtained by standard or vascular cuffs was found. This study investigated the reliability of ABI measures using standard and vascular pressure cuffs. Two raters measured 480 systolic blood pressures of 10 healthy participants using standard and vascular cuffs. Intrarater reliability for standard cuffs was weak (intraclass correlation coeffi cient [ICC] ϭ 0.42-0.63)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(17 citation statements)
references
References 20 publications
0
17
0
Order By: Relevance
“…Notably, studies either implemented manual Doppler [ 24 , 30 , 33 , 38 ], sphygmomanometric methods [ 29 ], or automated oscillometry [ 30 , 31 ] in deriving ABPI scores. Manual methodological approaches in ascertaining ABPI posit a degree of observer bias [ 45 ]. ABPI score inaccuracies may have been present since the observer must measure ankle and brachial pressures simultaneously rather than successively [ 45 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Notably, studies either implemented manual Doppler [ 24 , 30 , 33 , 38 ], sphygmomanometric methods [ 29 ], or automated oscillometry [ 30 , 31 ] in deriving ABPI scores. Manual methodological approaches in ascertaining ABPI posit a degree of observer bias [ 45 ]. ABPI score inaccuracies may have been present since the observer must measure ankle and brachial pressures simultaneously rather than successively [ 45 ].…”
Section: Discussionmentioning
confidence: 99%
“…Manual methodological approaches in ascertaining ABPI posit a degree of observer bias [ 45 ]. ABPI score inaccuracies may have been present since the observer must measure ankle and brachial pressures simultaneously rather than successively [ 45 ]. Despite reducing the risk of observer bias, no evidence was found validating automated oscillometry in an RA population.…”
Section: Discussionmentioning
confidence: 99%
“…Eleven studies reported participants' gender, with more men ( n = 416, 56.4%) overall than women, whilst gender was unreported in four studies [12, 46, 49, 50]. Most of the studies included predominantly older participants (age range (41–92 years) [12, 13, 16, 47–49, 51, 53–55, 57], however two studies recruited only younger adults (age range 22–30 years) [46, 56], one study included 18–80 year olds [52] and one study did not report participants' ages [50]. The majority of studies [12, 47–51, 55, 57] included only participants with suspected PAD, or risk factors for atherosclerosis; three studied a mixed population including those without risk factors or clinical indicators of PAD [13, 16, 52]; two studies included only participants with diabetes [53, 54], and two studies included only healthy individuals [46, 56].…”
Section: Resultsmentioning
confidence: 99%
“…There was little consistency in the training and qualifications of the raters used, with experience ranging from students [46, 47] to experienced vascular technicians and/or vascular specialist doctors [12, 13, 48, 54, 57]. Six studies did not state the background of the personnel performing the test [49, 51–53, 55, 56]. The majority of the studies used Doppler and manual sphygmomanometer to measure systolic blood pressures; [12, 13, 16, 46–49, 51–53, 56] however three studies used an automated device to obtain some or all of the pressure readings [54, 55, 57] and one study did not report the method used [50].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation